Analisis Produk dan Proses Produksi Bioetanol Limbah Batang Tembakau - Muhammad Ikwan; Ikhwanul Qiram; Anas Mukhtar (Virtual of Mechanical Engineering Article, 2022)
Tobacco stems contain up to 35-50% cellulose, make them ideal for use as a renewable energy source. Tobacco varieties Na Oogst and Voor Oogst are characterized by their growing season. This study aims to obtain the effect of comparison of tobacco variants on the characteristics of bioethanol products. Each type is distinguished by its particle size (a) : 8-10 mm, (b) : 1.19 mm, (c) : 0.25 mm. A total of 100 grams of material was delignified using 1 liter of 4% HCl for 30 minutes. The material is then fermented using 10 grams of yeast for 10 days and distilled at a temperature of 78-80oC. Using Image J Software, the volume of the product is measured and then burned to examine the characteristics of the fire based on the duration of the flame, the percentage of color, and the dimensions of the flame. The volume of the product is also affected by particle size. The Na Oogst variant had the maximum volume with a particle size (c) of 120 ml and the lowest volume with a particle size (a) of 29 ml. The best fire characteristics were obtained in the Voor Oogst variant with particle size (c) and a blue flame percentage of 48 percent, whereas the Na Oogst variant with particle size (a) and a blue flame percentage of 10.2 percent had the lowest blue flame percentage.